Assessment of Florpyrauxifen-benzyl Potential to Carryover to Subsequent Crops. (7th June 2018) - Miller, M. Ryan; Norsworthy, Jason K.
Abstract: Florpyrauxifen-benzyl is a new synthetic auxin herbicide that will provide a novel site of action in rice production. In many areas of the United States it is common practice to plant soybeans in rotation with rice, thereby introducing the potential for herbicide carryover. Multiple field experiments were conducted in 2014 and repeated in 2015 to evaluate potential plant-back restrictions for soybean and other row crops following an application of florpyrauxifen-benzyl. In the first experiment, treatments comprised florpyrauxifen-benzyl applied at 40 followed by 40 g ai ha –1, 80 fb 80 g ai ha –1, and a nontreated check. In 2014, herbicides were applied to a silt loam soil near Stuttgart and Colt, AR, and fields remained fallow following application. The following year, corn, cotton, soybean, grain sorghum, and sunflower were planted within the previously treated area. Stand counts, crop heights, and visual injury assessments were done for each crop following planting, and aboveground biomass data were collected 28 d after planting. No significant differences were observed among the treatments for any of the parameters assessed, highlighting the rotational flexibility of common row crops 1 yr following a florpyrauxifen-benzyl application. In the second experiment, florpyrauxifen-benzyl was applied at 30 and 60 g ai ha –1 at 56, 28, 14, and 0 d before planting soybean. Injury assessments corresponded to the highest concentration of florpyrauxifen-benzyl and its metabolites recovered from soil at the time of planting. Conversely, soybean injury was reduced when florpyrauxifen-benzyl was applied at increasing intervals before planting. At the end of each season, soybean yield was similar to the nontreated control when florpyrauxifen-benzyl at 30 or 60 g ai ha –1 was applied 56 d before planting, whereas all other treatments reduced yield. These results support a relatively short replant interval for soybean after florpyrauxifen-benzyl application to rice.